Advances and Strategies in Biosensor-Based Diagnostics for Parasitic Infections: A Comprehensive Scoping Review - Aminizadeh, Selva; Alizadeh, Gita; Alizadeh, Zahra; Khalilzadeh, Balal; Abidin, Zurina Zainal; Marzi, Mahdi; Rafiei-Sefiddashti, Raheleh (Springer, 2026)
Parasitic diseases are among the most widespread infections worldwide, causing millions of deaths and illnesses each year. So rapid and accurate diagnosis is essential, requiring highly sensitive and specific tests. Biosensors can provide significant advantages over traditional diagnostic methods because of their specificity, sensitivity, speed, simplicity, ease of use, repeatability, and capacity for early-stage disease detection. Recent advances in modern diagnostic tools for detecting parasitic infections use nanomaterials such as gold nanoparticles, carbon nanofibers, and carbon nanotubes. These developments have significantly lowered detection limits to the picogram and femtogram levels. This review will cover recent advancements in biosensor-based diagnostic techniques in parasitology.
Keywords: Biosensor; Diagnosis; Parasitic Diseases; Early-Stage Evaluation